Improvisation and Learning Processes in Organizations: a metaphor applying the Brazilian rhythm choro - Flach, Leonardo; Antonello, Claudia Simone (Organizações & Sociedade, 2014)
Whereas improvisation has been discussed in international literature mainly from the metaphor of jazz and theater, this essay discusses how the phenomenon of improvisation can contribute to new interpretations of Organizational Learning. We use the metaphor of improvisation in the Brazilian rhythm ‘Choro’ in order to understand the process of improvisation in organizations. Thus, the main objective of the study is to discuss and analyze the role of improvisation in the Organizational Learning process. In the fi nal considerations, we conclude that improvisation plays a signifi cant role in the processes of Organizational Learning. Thus, we argue that the socio-cultural approach in Organizational Learning can help to understand the process of improvisation, with the role of communities of practice, culture, social practices and sensemaking in this phenomenon.